Comparative Pharmacokinetics of Cinobufacini Capsule and Injection by UPLC-MS/MS - Li, Ming; Qin, Yanhong; Li, Zhe; Lan, Jinshuai; Zhang, Tong; Ding, Yue (Frontiers in Pharmacology, 2022)
Cinobufacini capsule and injection are two different formulations from same source, the boiling water extraction of the skin of Bufo bufo gargarizans Cantor, which have been approved by the Chinese State Food and Drug Administration (CFDA) for the treatment of various cancers. Our previous study has found Cinobufacini capsule and injection exhibited different anticancer effects, but their different pharmacokinetics behaviors which could give a cause of that have never been reported. So a sensitive and selective method for simultaneous quantitation of thirteen compounds in rat plasma, including bufothionine, helllebrigenin, bufalin, gamabufotalin, telocinobufagin, cinobufagin, arenobufagin, cinobufotalin, desacetylcinobufotalin, bufotaline, pseudobufarenogin, resibufogenin and desacetylcinobufagin was established by using the Aglient 6460 mass spectrometer equipped with ESI ion source in a multi-reaction monitoring (MRM) mode. Chromatographic analysis was accomplished in 6 min by using an Agilent SB-C18 column and a mobile phase consisting of 0.1% formic acid in water and acetonitrile in an optimized gradient program at a flow rate of 0.3 mL/min. The correlation coefficients (r) of all analytes ranged from 0.9967 to 0.9996, while their lower limits of quantification ranged from 0.20 to 4.84 ng/mL. The method has been fully verified and applied for the pharmacokinetic differences study of Cinobufacini capsule and injection in rats. The results showed nine components could be quantitated in rats plasma samples after administration of Cinobufacini capsule, while only bufothionine, bufalin, arenobufagin and pseudobufarenogin could be detected in Cinobufacini injection group. Their pharmacokinetic studies indicated telocinobufagin, bufalin, desacetylcinobufagin and arenobufagin were predicted as the potential active substances of Cinobufacini capsule, while bufothionine were considered as major ingredients in Cinobufacini injection due to their relatively high blood drug exposure. And the AUC of the nine components in Cinobufacini capsule groups with three different doses, showed a similar trend with significant differences, and the exposure increased with the increase of dose. The pharmacokinetic characteristics of all major ingredients in Cinobufacini capsules and injection were of wide variation, which could be used to explain differences in efficacy of the Cinobufacini capsule and injection and infer the pharmacodynamic ingredients of various Cinobufacini preparations.